Feasibility, quality and validity of narrative multisource feedback in postgraduate training: a mixed-method study - Maurice A Lembeck; Jette Led Sørensen; Hanne Pedersen; Ellen Astrid Holm; Shaymaa Jaafar Lafta Al-Bayati; Toke Seierøe Barfod; Emilie Ramberg; Åse Kathrine Klemmensen (BMJ Open)
Objectives To examine a narrative multisource feedback (MSF) instrument concerning feasibility, quality of narrative comments, perceptions of users (face validity), consequential validity, discriminating capacity and number of assessors needed.Design Qualitative text analysis supplemented by quantitative descriptive analysis.Setting Internal Medicine Departments in Zealand, Denmark.Participants 48 postgraduate trainees in internal medicine specialties, 1 clinical supervisor for each trainee and 376 feedback givers (respondents).Intervention This study examines the use of an electronic, purely narrative MSF instrument. After the MSF process, the trainee and the supervisor answered a postquestionnaire concerning their perception of the process. The authors coded the comments in the MSF reports for valence (positive or negative), specificity, relation to behaviour and whether the comment suggested a strategy for improvement. Four of the authors independently classified the MSF reports as either ‘no reasons for concern’ or ‘possibly some concern’, thereby examining discriminating capacity. Through iterative readings, the authors furthermore tried to identify how many respondents were needed in order to get a reliable impression of a trainee.Results Out of all comments coded for valence (n=1935), 89% were positive and 11% negative. Out of all coded comments (n=4684), 3.8% were suggesting ways to improve. 92% of trainees and supervisors preferred a narrative MSF to a numerical MSF, and 82% of the trainees discovered performance in need of development, but only 53% had made a specific plan for development. Kappa coefficients for inter-rater correlations between four authors were 0.7–1. There was a significant association (p<0.001) between the number of negative comments and the qualitative judgement by the four authors. It was not possible to define a specific number of respondents needed.Conclusions A purely narrative MSF contributes with educational value and experienced supervisors can discriminate between trainees’ performances based on the MSF reports.